Analisis SWOT dalam Peningkatkan Mutu Sekolah - John Suarlin (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
The development of the world of education is the responsibility of all educational staff by improving the quality of education. Student success is a benchmark for the quality provided by the school. Elementary school is a basic level of education where the quality of education must be really considered, because students must have good character in order to develop optimally. SDN What stands out most is that the role of school principals must be increased so that the quality of education can improve, because school principals must direct educational staff in adapting learning programs to suit the curriculum determined by the government. Quality education cannot come by itself, it must be done with careful planning and in accordance with the targeted goals. Therefore, methods or analysis are needed that can determine the best strategy for improving the quality of education. SWOT analysis (Strength, Weakness, Opportunities, Threats) is an analysis based on the internal and external strengths of an organization or agency. SWOT analysis can be used as a strategy to improve the quality of education. Based on the results of research conducted, schools must take advantage of existing strengths and opportunities to compete as the best school in Bukit Timah, but there are still things that need to be improved to achieve this, such as expanding teachers' knowledge of the latest curriculum, updating existing facilities and so on. On the other hand, by taking advantage of the school's strengths and existing school opportunities, the school can improve the quality of the school to be even better